Pengimplementasian Sistem Digital Dalam Meningkatkan Aksesibilitas dan Efisiensi Pelayanan Kesehatan di Rumah Sakit - Alawi, Alwan; Ariyani, Nurul Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
In today's digital era, a system must be developed according to the needs and demands of the community, the implementation of digital systems in the field of health services has brought significant transformation in improving the accessibility and efficiency of health services. This study explores the positive impact of implementing digital technologies in health services such as online registration, electronic medical records, and health applications on health services. Quantitative research methods were used by analyzing internal hospital data, such as interviewing health care staff in using digital systems to measure the efficiency of basic health services, to find out the environmental factors on the efficiency of basic health services. The results show that the use of digital technology has enabled patients to access health services more easily, reduced waiting times, and improved care coordination. Although challenges such as data security and technology access gaps still exist, strategic measures in digital infrastructure development and improved digital literacy can overcome these barriers. This research supports the importance of continuing to encourage technological innovation in healthcare to improve the overall quality of life of the community.